Report of the Aboriginal Justice Inquiry of Manitoba, vol. 1, The Justice System and Aboriginal People - Manitoba Public Inquiry into the Administration of Justice and Aboriginal People (Public Inquiry into the Administration of Justice and Aboriginal People, 1991)
The Aboriginal Justice Inquiry was created in response to two specific incidents: the death of Helen Betty Osborne and John Joseph Harper. These were separate incidents but were seen by many as troubling examples of the manner in which Manitoba's justice system was failing Aboriginal people. The scope of the inquiry was to include all components of the justice system, that is, policing, courts, and correctional services. The Commission considered whether Aboriginal and non-Aboriginal peoples were treated differently by the system and whether there were specific adverse effects, including possible systemic discrimination against Aboriginal people. The final written report is a thorough review.